2011
DOI: 10.1080/10942911003637319
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Frictional Properties of Popcorn Kernel as Affected by Moisture Content

Abstract: Strength properties and dynamic coefficient of friction of popcorn kernels were evaluated as a function of moisture content in the range of 7.78-16.72 g/100 g dry solids. In order to determine strength properties of the kernels that are in terms of deformation at rupture point, rupture force, energy absorbed, hardness, and toughness of the popcorn kernels were quasi-statically loaded between two parallel plates. To determine frictional properties, friction tests were performed on aluminum, steel, and fiberglas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Typical kinds of grain damage are mechanical damage and chemical damage. Mechanical grain damage is due to the impact of grain kernels and rigid surface of threshing unit of high relative speed [32][33][34][35] . The method of high-speed digital imaging has been used to find the morphological and textural characteristics of three views of grain when grain kernels free fall and impact [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Typical kinds of grain damage are mechanical damage and chemical damage. Mechanical grain damage is due to the impact of grain kernels and rigid surface of threshing unit of high relative speed [32][33][34][35] . The method of high-speed digital imaging has been used to find the morphological and textural characteristics of three views of grain when grain kernels free fall and impact [36] .…”
Section: Introductionmentioning
confidence: 99%
“…More tests about texture should be carried out to conclude about a possible effect of the RF-based protocol, as the hardness obtained seems to be related to high variability on the yellow corn grains. Kalkan et al (2011) found that, in general, strength properties in popcorn kernel decreased with increasing moisture content.…”
Section: Resultsmentioning
confidence: 93%
“…The moisture content values of RF‐treated samples mean around 9 g water 100 g −1 dry solids, which is higher than that reported by Kalkan et al . (2011) for popcorn kernel variety Nermin‐cin in the Mediterranean area, with a value of 7.78 g water 100 g −1 dry solids. Thus, despite the moisture content decreased with the RF treatment, it is still adequate for commercialization and further processes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Singh et al (1991) tested the elastic modulus and Poisson's ratio under different moisture contents and revealed the stress and strain law of kernel detachment. Kalkan et al (2011) found that the strength values of popcorn decreased with increasing moisture content by measuring strength properties and the dynamic coefficient of friction. Ajayi and Clarke (1997) found that moisture content had the most significant effect on the strength characteristics of the corn kernel by assessing the energy of impact loss.…”
Section: Introductionmentioning
confidence: 99%